The Challenges of Taking TOEIC Test and How to Overcome: Perception of Indonesian Vocational Students - Nurul Amalia Zahruni; Fahmi Fahmi; Bambang Widi Pratolo (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
The purpose of this research was to discover problems that Indonesian Vocational Students are having with the Test of English for International Communication (TOEIC) to improve TOEIC instruction. The participants were 18 students in school attending the TOEIC preparation course in the TOEIC course in October 2018. There were two steps in taking the data: (1) questionnaires on the listening and reading problems in the TOEIC test, and (2) interview on how they cope with the problems. The result shows that: 1) The majority of subjects had no experience in TOEIC and most of them did not have any preparation for the test; 2) Listening problems were at a high level in questionnaires 100% for the lack in vocabulary; 3) Reading problems were at a high level in questionnaires 100% for unknowing the meaning based on the context of the text; 4) The interview results showed that the students solve the problem in TOEIC test with learning by themselves, discuss with a partner and learning on the internet. The researchers recommend that the TOEIC course should include vocabulary building and be conducted frequently.